PELATIHAN PENGEMBANGAN DAN IMPLEMENTASI GAME EDUKASI SEBAGAI MANAJEMEN MEDIA PEMBELAJARAN DI SMP NEGERI 2 SUNGAI BEREMAS KAB.PASAMAN BARAT - Agus Nurofik; Lina Tio; Reni Wijaya; Sutiyem, Sutiyem; Hendrik Permana (Bajang Institute, 2025)
Learning using computer-based learning multimedia can increase students' learning motivation. One of them is by using digital educational games. However, the use of computer-based subject learning media at SMP Negeri 2 Sungai Beremas is still limited. This study aims to develop digital educational games as learning media on the material of classification of living things. Method: The development of learning media refers to the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). Results: After going through a series of trials, the product was considered